2020
DOI: 10.1111/ijcs.12624
|View full text |Cite
|
Sign up to set email alerts
|

Religiosity and food waste reduction intentions: A conceptual model

Abstract: Are religious consumers less wasteful? If so, to what extent and by what mechanisms does religiosity motivate consumers to reduce food waste? To address these questions, this study proposes a conceptual model and evaluates it empirically using PLS‐SEM and data from 583 consumers. The results reveal that religiosity encourages food waste reduction. Specifically, religiosity is positively related to consumer attitudes, activism and personal and subjective norms to reduce food waste. Consumers’ activism and perso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
66
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 72 publications
(68 citation statements)
references
References 77 publications
1
66
1
Order By: Relevance
“…On the other side, Visschers et al [55] argued that behavioral intentions of prohibiting food waste could predict food waste behavior. More specifically, studies confirmed a positive and direct relationship between personal attitude and food waste reduction intention [5,13,54]. This is due to the advantages perceived by individuals of reducing food waste, like saving money .…”
Section: The Role Of Attitude In the Relationship Between Religiosity/food Consumption Culture And Food Waste Intentionmentioning
confidence: 72%
See 4 more Smart Citations
“…On the other side, Visschers et al [55] argued that behavioral intentions of prohibiting food waste could predict food waste behavior. More specifically, studies confirmed a positive and direct relationship between personal attitude and food waste reduction intention [5,13,54]. This is due to the advantages perceived by individuals of reducing food waste, like saving money .…”
Section: The Role Of Attitude In the Relationship Between Religiosity/food Consumption Culture And Food Waste Intentionmentioning
confidence: 72%
“…The food waste literature has shown some established factors that influence food waste intention and motivates people to reduce wasted food. Among the motives for reducing wasted food, the role of religiosity gained the attention of researchers but this research area is still under research [13]. Religiosity is one of the key components of social behavior and directly and indirectly influences consumers and society [16].…”
Section: Religiosity and Food Waste Intentionmentioning
confidence: 99%
See 3 more Smart Citations